2009
DOI: 10.1590/s1516-84842009005000054
|View full text |Cite
|
Sign up to set email alerts
|

Perfil do doador de sangue autoexcluído no Hemocentro Regional de Uberaba-MG (HRU) no período de 1996 a 2006

Abstract: Candidatos a doação são submetidos a triagem clínica e sorológica para minimizar o risco de transmissão de doenças via transfusão. Uma de suas limitações é a janela imunológica, que possibilita a transfusão de sangue contaminado. O objetivo deste trabalho foi avaliar o índice de autoexclusão de acordo com idade, gênero, estado civil, cor e tipo de doação, as variações anuais de autoexcluídos e sua eficácia em evitar a transfusão de sangue contaminado. Os dados foram analisados através do teste qui-quadrado, od… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
10

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 5 publications
(14 reference statements)
1
16
0
10
Order By: Relevance
“…The independent variables included gender (male or female), age (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), 36-45 and 46-65 years), education level (complete or incomplete primary or secondary school), residence region (from the seven major geographical regions of the state: Florianópolis, Extremo Oeste, Meio Oeste, Planalto Norte, Sul, Vale do Itajaí and Planalto Serrano) and previous blood donation status (never, within previous 12 months or more than 12 months ago). This model allowed for an estimation of the syphilis infection probability among those donors who did not return for follow-up testing, despite a reactive screening test result.…”
Section: Methodsmentioning
confidence: 99%
“…The independent variables included gender (male or female), age (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), 36-45 and 46-65 years), education level (complete or incomplete primary or secondary school), residence region (from the seven major geographical regions of the state: Florianópolis, Extremo Oeste, Meio Oeste, Planalto Norte, Sul, Vale do Itajaí and Planalto Serrano) and previous blood donation status (never, within previous 12 months or more than 12 months ago). This model allowed for an estimation of the syphilis infection probability among those donors who did not return for follow-up testing, despite a reactive screening test result.…”
Section: Methodsmentioning
confidence: 99%
“…As for the prevalence of VDRL, HTLV and T. cruzi, most of the studies from other Brazilian blood banks showed more elevated figures Dourado et al, 2003;Sobreira et al, 2001;Melo et al, 2009;Moraes-Souza et al, 2006;Martins et al, 2009).…”
Section: Resultsmentioning
confidence: 96%
“…[6][7] Thus, candidates for blood donation undergo clinical and serological screening to minimize the risk of disease transmission via transfusion. 8 The country´s blood banks adopt measures as questionnaires about the general medical condition and exposure to sources of infection (hemodialysis, intravenous drug use, promiscuity); performing rigorous tests in all donated blood for tracing transmissible diseases. The presence of risk factors and seropositivity for blood transmissible diseases involve the immediate disposal of blood bags.…”
Section: Introductionmentioning
confidence: 99%
“…In the transfusion, one of the limitations is the immunological window, which allows contaminated blood transfusion. 8 In Brazil, until June 2014, it was reported in the System Born informatio--SINAN NET, 70,677 cases of infection by the human immunodeficiency virus (HIV) among adults and 773 in children. 12 As to transmission among the older than 13 years old, sexually prevails.…”
Section: Introductionmentioning
confidence: 99%